(untitled) (Revista Argentina de Musicología, 1996)
Book review: Gerard Béhague: Heitor Villa-Lobos: The Search for Brazil’s musical Soul. Austin, Texas: Institute of LatinAmerican Studies,University of Texas at Austin, 1994. Prefacio de Vasco Mariz. xvii+202 págs.